Combined Effect of Air Pollution and Genetic Risk on Incident Cardiovascular Diseases - Tae‐Min Rhee; Yunmi Ji; Seokhun Yang; Heesun Lee; Jun‐Bean Park; Hyung‐Kwan Kim; Yong‐Jin Kim; Juyong Brian Kim; Sungho Won; Seung‐Pyo Lee (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Whether genetic susceptibility to cardiovascular diseases (CVDs) enhances the vulnerability to adverse cardiovascular outcomes by air pollution is unknown. We assessed the combined effect of air pollution and genetic predispositions on CVD risk. Methods and Results From the UK Biobank cohort, we selected genetically unrelated White British participants without CVD. Levels of ambient particulate matter with a diameter of <2.5 μm (PM2.5) and <10 μm were estimated using land use regression models. An individual's genetic predisposition to CVDs was determined by polygenic risk scores for coronary artery disease, myocardial infarction, stroke, ischemic stroke, heart failure, and atrial fibrillation. We stratified mortality and CVD risk by PM2.5 exposure across high and low genetic risk groups. A total of 249 082 participants (aged 56.9±8.0 years, 46.8% men) were followed for a median of 10.8 years. The combined effect of PM2.5 exposure and the genetic predisposition of CVD demonstrated the highest risk of cardiovascular death in the high genetic risk group with the greatest PM2.5 exposure (adjusted hazard ratios ranging from 1.73 to 2.12 across the polygenic risk score of each CVD). The combination of higher exposure to ambient PM2.5 and high genetic risk was associated with higher incidence of all CVDs, although no significant interactions were observed between genetic risk and PM2.5 exposure on cardiovascular death or CVD events. Conclusions A combination of greater PM2.5 exposure and higher genetic predisposition to particular CVDs was modestly associated with elevated risks of cardiovascular death and CVDs. Not only alleviating PM2.5 exposure in the general population but also implementing individualized preventive approach for those at high genetic risk might be beneficial.